Educational Game about Drugs for Visually Impaired People: A Comparison between Brazil and Portugal - Mariano, Monaliza Ribeiro; Pagliuca, Lorita Marlena Freitag; Oliveira, Paula Marciana; Almeida, Paulo César; Aguiar, Adriana Sousa C.; Abreu, Wilson (Scientific Research Publishing, 2017)
Objective: To validate the educational board game “Drugs: playing fair” for visually impaired people in Brazil and Portugal. Methods: Study of apparent validation carried out in two associations for visually impaired people in Fortaleza, Brazil, and in Porto, Portugal. Thirty-six visually impaired people, 18 from each country, participated in the study. An evaluation tool with 23 items on specifications, content and motivation of the game was applied. Results: The scores awarded in both countries were excellent, with means varying in Brazil from 9.0 to 9.6 and in Portugal, from 8.4 to 9.2. As for the categories and subcategories, the best means in Brazil were: content (9.5); theoretical and methodological consistency (9.6) and concepts/information (9.5). In Portugal, the best means were concepts/information (9.2) and curiosity (9.2). Only two items showed a significant difference: “it allows interaction” (p = 0.024) and “compatible degree of difficulty” (p = 0.012). Conclusion: The educational game on drugs was validated in Brazil and Portugal.
Keywords: Validation Studies; Health Promotion; Nursing; Visually Impaired Persons